ANALISIS USAHA INDUSTRI CAPING BAMBU SKALA RUMAH TANGGA DI KABUPATEN MAGETAN - Sari, Vella Anggita; Marwanti, Sri; Khomah, Isti (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2020)
This study purpose to find out the cost, revenue, profit, profitability, efficiency, and business risk of bamboo caping home industry in Magetan Regency. The basic method used in this research was descriptive. The determination of the sample area was purposive. The determination of respondents was done by purposive sampling. The result of the research shows the average total cost by craftsmen in Magetan Regency is IDRi7,091,977.00/month, blengker IDR 288,513.00/month, halusan-kasaran woven IDR 195,838.00/month, kepangan woven IDR 229,286.00/month and gilikan IDR 6,803,464.00/month. The average revenue by craftmen is IDR 9,217,160.00/month, blengker IDR 382,160.00/month, halusan-kasaran woven IDR 422,750.00/month, kepangan woven IDR 454,400.00/month and gilikan IDR 8,835,000.00/month so that the average profit is IDR 226,912.00/month, blengker IDR 93,647.00/month, halusan-kasaran woven IDR 226,912.00/month, kepangan woven IDR 225,114.00/month and gilikan IDR 2,031,536.00/month. Profitability is 30%, blengker 32,5%, halusan-kasaran woven 115,9%, kepangan woven 98,2%, and gilikan 29,9%. R/C ratio more than 1, that is 1,30 blengker 1,32; halusan-kasaran woven 2,16; kepangan woven 1,98 and gilikan 1,30 mean its efficient. The coefficient variation more than 0,5 that is halusan-kasaran woven 0,51; and kepangan woven 0,55 and the low profit limit (L) is less than 0, so the bamboo caping industry is at risk.